Effects of Socio-Economic Factors on Entrepreneurship Activities in Cape Coast, Ghana (Journal of Entrepreneurship and Business, 2021)
Entrepreneurship involves the creation of jobs and wealth in the economy, normally through a small business management. There may be problems in performing these functions by entrepreneurs, because of certain factors, which affect their involvement in entrepreneurial activities. The objective of this study is to assess the impact of socio-economic factors on entrepreneurial activities in Cape Coast, Ghana. A simple random sampling method is used to select 181 entrepreneurs from Cape Coast for the study. The Structural Equation Model-Partial Least Square version 2.0 is used for the analysis. The finding reveals that inflation, high tax rate, religion, and life style of the entrepreneurs significantly influence their entrepreneurial activities and performance. The study concludes that for a successful entrepreneurship performance to be achieved, there is a need for good socio-cultural conditions and sound economic policies to be put in place. The study recommends that the government should reduce the interest rate to make borrowing flexible to entrepreneurs and a lower tax regime should be commenced to encourage low-level income earners to have access to funding for entrepreneurship activities in Cape Coast, Ghana.
Keywords: Array; Array; Array; Array